Fluid mineralization of the Dongtongyu gold deposit in the southern margin of North China craton: Evidence from microthermometry and composition of fluid inclusions - Wei, Hao; Xu, Liangwei; Li, Dong; Feng, Yunlei; Wu, Xiaogui; Chang, Honglun; Wang, Duixing; Liu, Zhuo; Du, Wenbiao (Frontiers in Earth Science, 2023)
In this study, petrographic, microthermometric, and synchrotron radiation X-ray fluorescence (SRXRF) analyses of fluid inclusions were conducted to shed light on the mineralization mechanism of the Dongtongyu deposit and provide some evidence of the relationship among CO2, Au, and other ore elements (e.g., Cu, Fe, Zn, and Pb) in ore-forming fluids. The ore-forming fluid is characterized as the H2O–CO2–NaCl system with medium–high temperatures and low salinities. Four structural mineralization stages are distinguished: Pyrite–quartz (Stage 1), gold–quartz–pyrite (Stage 2), gold–quartz–polymetallic sulfide (Stage 3), and quartz–calcite (Stage 4). Fluid inclusions in Stages 1–3 are dominated by the H2O–CO2 type, and most of them contain liquid H2O and liquid CO2 at room temperature. The melting temperatures (Tm-CO2 = −82.1℃ to −57.5℃) of solid CO2 in Stage 1 are relatively low. The values of Tm-CO2 in Stages 2–3 are quite close, with ranges of −60.5℃ to −56.5℃ and −59.2℃ to −58.6℃, respectively. The melting temperatures of clathrate in Stages 1–3 are −2.7℃ to +7.8℃, −5.5℃ to +7.8℃, and +3.7℃ to +7.2℃. The homogenization temperatures of the CO2 phase in the H2O–CO2 inclusions of the three stages are measured as −7.5℃ to +31.7℃, −7.5℃ to +29.3℃, and 7.1℃ to +24.1℃. The total homogenization temperatures in Stages 1–3 are 180℃–394℃, 202℃–305℃, and 224℃–271℃, with salinities of 4.3 wt.%–18.2 wt.% NaCl, 4.3 wt.%–20.0 wt.% NaCl, and 5.3 wt.%–11.0 wt.% NaCl, respectively. The laser Raman spectroscopy results show that the CO2–H2O inclusions in the quartz veins contain abundant CO2 and CH4. The SRXFR results show that most of the elements, especially As, Te, and Cu, are more enriched in liquid CO2 than in liquid H2O. The elements of Au, Fe, Ni, Cu, and Pb have higher concentrations in H2O–CO2-type fluid inclusions in Stage 2 than other fluid inclusions in Stages 1–2, suggesting that gold mineralization is closely related to CO2-rich fluids. During the fluid evolution process, fluid immiscibility is an important mineralization mechanism of gold. The increase in CO2 and CH4 and the decrease in the fluid temperature might promote fluid immiscibility.